2018
DOI: 10.1111/joim.12826
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors and risk of iron deficiency: a population‐based case–control study

Abstract: Chronic PPI use increases the risk of ID. Physicians should consider this when balancing the risks and benefits of chronic PPI prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
(59 reference statements)
2
33
1
1
Order By: Relevance
“…In our univariate Cox proportional hazards models, PPI use and solid organ transplantation were identified as risk factors for development of IDA during ECP therapy, while heparin use (over citrate) was associated with reduced risk. Iron absorption is partially dependent on acidic pH, and as PPIs can induce a hypo‐ or achlorhydric state, chronic PPI use has been implicated in the development of iron deficiency . The potential for diminished gastrointestinal absorption, coupled with presumed iron loss from ECP therapy, may explain why PPI use was identified as a risk factor for IDA in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In our univariate Cox proportional hazards models, PPI use and solid organ transplantation were identified as risk factors for development of IDA during ECP therapy, while heparin use (over citrate) was associated with reduced risk. Iron absorption is partially dependent on acidic pH, and as PPIs can induce a hypo‐ or achlorhydric state, chronic PPI use has been implicated in the development of iron deficiency . The potential for diminished gastrointestinal absorption, coupled with presumed iron loss from ECP therapy, may explain why PPI use was identified as a risk factor for IDA in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…An older, small cohort study of the effects of 1 year of PPI therapy in cases versus controls yielded ORs of 5.03 for a decrease in haemoglobin, and of 5.46 for a fall in haematocrit; this was a PPI class effect . The recent large studies showed that the risks reached a plateau at a medium dose and at a duration of use of 2 years , and improved when PPI use was discontinued. Risks were similar during time periods when PPIs were available solely by prescription or when PPIs were also available over the counter .…”
mentioning
confidence: 98%
“…For over a decade, despite animal and human studies and numerous case reports that demonstrated interference by proton pump inhibitors (PPIs) with enteric absorption of dietary and medicinal iron, the importance of this effect in clinical practice has remained uncertain . With the publication in this issue of a large, well‐controlled, UK‐based population study , strongly supported by another similarly large study from the USA , the risks of PPI‐induced iron deficiency (ID) have been definitively established. The UK database study, by authors from the Netherlands, showed that in full (continuous for >1 year) and partial (intermittent) long‐term users of PPIs, adjusted odds ratios (ORs) for developing ID compared to non‐users were approximately 3.6 and 1.5, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations